Evaluation of patients with diffuse unilateral subacute neuroretinitis by spectral domain optical coherence tomography with enhanced depth imaging - Berbel, Rodrigo F (Dove Medical Press, 2014)
BACKGROUND: The purpose of this study was to determine the value of spectral domain optical coherence tomography (SD-OCT) in assessing patients with diffuse unilateral subacute neuroretinitis (DUSN). METHODS: This was an observational case series with clinical imaging correlation performed at the Retina and Vitreous Institute of Londrina and State University of Londrina, Paraná, Brazil. The series comprised ten consecutive patients with a confirmed diagnosis of DUSN, ie, seven patients with late-stage disease and three with early-stage disease, who were assessed by SD-OCT for mean macular, retinal nerve fiber layer, and choroidal thickness using enhanced depth imaging software. RESULTS: Comparing the affected eye with the healthy fellow eye, significant diffuse atrophy of the retinal layers with a decrease in mean macular (P=0.004) and retinal nerve fiber layer (P=0.002) thickness was found in all cases. There was no difference in choroidal thickness (P=0.262). CONCLUSION: The correlation of SD-OCT results with central vision and funduscopic findings may explain the profound loss of visual function in patients with DUSN.